EXPLORING PRE-SERVICE TEACHERS’ EXPERIENCES ON PEDAGOGICAL INNOVATION IN ELT ACROSS SOUTHEAST ASIAN COUNTRIES - Koesoemo Ratih (PUPIL: International Journal of Teaching, Education and Learning, 2026)
This study explored the experiences of pre-service teachers in implementing pedagogical innovation during their teaching practice in South East Asia (SEA) Teacher program. Using a qualitative case study design, data were collected through questionnaires, two online Focus Group Discussions and follow-up interviews with 10 pre-service teachers. Phenomenological content analysis was employed to capture participants’ lived experiences, focusing on types of innovation during their teaching practice, the factors that mostly support their innovation and challenges in implementing the innovation. The participants reported that real-world tasks and instructional material using engaging media either adopting technology or not which were presented in systematic and purposeful ways, facilitated deeper learning, while challenges included poor school facilities, unworking lesson plans, generational gap, and uneven students’ participation. The study underscores the theoretical grounding of innovative pedagogy in constructivism highlighting its potential as a holistic pedagogical model that integrates cognitive, social, technological and motivational development. Practical implications suggest structured planning, scaffolding, and reflective assessment to optimize innovative pedagogy implementation in EFL contexts in Southeast Asia.